1968
DOI: 10.1111/j.1365-2621.1968.tb03626.x
|View full text |Cite
|
Sign up to set email alerts
|

Collagen and Elastin in Different Cuts of Veal and Beef

Abstract: and histological analysis are discussed from the standpoint of their nutritional significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1969
1969
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…This was surprising given that previous studies had demonstrated that longer periods of cooking solubilise the connective tissues, decrease hardness and make the denatured protein more accessible to digestive enzymes [8,29]. However, in our study, the comparatively lower collagen content of the sampled beef cut [30] prevented our ability to draw firm conclusions.…”
Section: Discussioncontrasting
confidence: 63%
“…This was surprising given that previous studies had demonstrated that longer periods of cooking solubilise the connective tissues, decrease hardness and make the denatured protein more accessible to digestive enzymes [8,29]. However, in our study, the comparatively lower collagen content of the sampled beef cut [30] prevented our ability to draw firm conclusions.…”
Section: Discussioncontrasting
confidence: 63%
“…These samples were analyzed chemically for collagen and elastin content. Insoluble collagen and elastin were extracted by the procedure of Vognarova et al (1968). The insoluble collagen fraction and elastin residue were hydrolyzed with 6 N HC1 in sealed tubes at 120 to 125 C for 4 h. Hydroxyproline content of the digesta Cscore of 10 = very tender or very juicy, 1 = very tough or very dry.…”
Section: Methodsmentioning
confidence: 99%
“…collagen than all older groups. Vognarova et al (1968) reported that veal muscle had a higher percentage of collagen than beef muscle. In ~< addition, our 9-mo group had more (P<.05) elastin than all older groups.…”
Section: Histological Evaluation Of Collagen Andmentioning
confidence: 99%
“…Similar values have been found for the skin of mice (Harkness, Harkness & James, 1958) and rats (Anasuya & Narasinga Rao, 1970). Although the collagen content of bovine muscle, bone and various organs is known (Neuman & Logan, 1950;Goll et al 1963;Vognarova, Dvorak & Bohm, 1968), this is the first direct estimate of the collagen content of the whole body of a calf. Indeed, although the collagen content of mammals is often quoted as 30-35 % of the total body protein (Seifter & Gallop, 1966), few direct estimates appear to exist.…”
Section: Collagen Distributionmentioning
confidence: 99%
“…Harkness et al (1958) found that collagenous-N formed 15-20% of the total-N in mice but Anasuya & Narasinga Rao (1970) reported higher values (23-32%) for rats. Many factors affect the collagen content of tissues such as the size (Harkness et al 1958), age (Vognarova et al 1968) and nutritional status (Anasuya & Narasinga Rao, 1970) of the animal. These factors could account for the high collagen content of the calves in the present study.…”
Section: Collagen Distributionmentioning
confidence: 99%